2014
DOI: 10.4187/respcare.03451
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxemia in Mechanically Ventilated, Critically Ill Subjects: Incidence and Related Factors

Abstract: BACKGROUND: Excessive supplemental oxygen causes injurious hyperoxemia. Before establishing the best P aO 2 targets for mechanically ventilated patients, it is important to understand the incidence of hyperoxemia and related factors. We investigated oxygenation in mechanically ventilated subjects in our ICU and evaluated factors related to hyperoxemia (P aO 2 > 120 mm Hg) at 48 h after initiation of mechanical ventilation. METHODS: We retrospectively reviewed the medical records of patients admitted to our ICU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 16 publications
0
21
1
2
Order By: Relevance
“…Consequently, clinicians are faced with the task of titrating the amount of oxygen delivered to avoid both hypoxemia and hyperoxemia. Prior studies show that clinicians appear to use higher FIO 2 than is necessary in the critically ill [3]. While the reasons are unclear, potential explanations include concerns over the need to avoid tissue hypoxia, [4,5] a desire to provide a "buffer" should a clinical deterioration occur, or because the consequences of hyperoxia are considered less severe than hypoxia.…”
Section: Oxygen Use In Ardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, clinicians are faced with the task of titrating the amount of oxygen delivered to avoid both hypoxemia and hyperoxemia. Prior studies show that clinicians appear to use higher FIO 2 than is necessary in the critically ill [3]. While the reasons are unclear, potential explanations include concerns over the need to avoid tissue hypoxia, [4,5] a desire to provide a "buffer" should a clinical deterioration occur, or because the consequences of hyperoxia are considered less severe than hypoxia.…”
Section: Oxygen Use In Ardsmentioning
confidence: 99%
“…While oxygen therapy can reverse tissue hypoxia, little evidence exists regarding the optimal use of oxygen in patients with ARDS. Critically ill patients frequently receive higher inspired oxygen concentrations than necessary [3], perhaps due to concerns regarding tissue hypoxia [4,5]. Hyperoxemia and the resultant tissue hyperoxia may worsen systemic organ injury in the critically ill. Arterial hyperoxemia has been associated with increased mortality in some older [6][7][8] but not more recent [9,10] studies of patients with acute brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…1,[44][45][46][47] Thus, current practice of supplemental oxygen administration is usually more liberal and may result in hyperoxaemia. [17][18][19][20]23,48,49 Recently, two metaanalyses of observational studies and a randomised clinical trial found an association between hyperoxaemia and mortality. 50,51,56 With the outlined systematic review, we aim to evaluate the benefits and harms of supplemental oxygen administration in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,45 Current practice of oxygen administration is usually liberal and may result in hyperoxaemia. [17][18][19][20]23,48,49 A systematic review of randomised trials in patients with acute myocardial infarction suggests a harmful effect of oxygen administration, but due to lack of power this was not conclusive. 32 Recently two meta-analyses of observational studies found an association between hyperoxaemia and mortality in critically ill patients.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
“…However, recently, more detailed factors for development of VILI have emerged: loading of alveolocapillary membrane, duration of exposure to MV, intensity of the exposure (tidal volume; Vt), end-expiratory pulmonary volume, magnitude of the available "baby lung" heterogeneity (which includes atelectasis, consolidation and edema) and hyperoxia. Endotoxin, vascular pressures and fluid/ transfusions are additional factors leading to VILI [2,3]. High Vt and high plateau pressure (Plat) can give excessive distension, or "stretch," of the aerated lungs, thus resulting in volutrauma and barotrauma.…”
Section: Introductionmentioning
confidence: 99%